Variation outside variable segments of the major outer membrane protein distinguishes trachoma from urogenital isolates of the same serovar of Chlamydia trachomatis. Issue 1 (February 1995) - Frost, E H; Deslandes, S; Gendron, D; Bourgaux-Ramoisy, D; Bourgaux, P
Abstract : OBJECTIVES--Whereas serovars A, B, Ba and C of Chlamydia trachomatis are usually associated with trachoma, two of these serovars (Ba and C) are occasionally observed in urogenital infections. Variation in the gene encoding the major outer membrane protein (MOMP) was explored to distinguish urogenital from trachoma specimens of the same serovar. METHODS--A large portion of the MOMP gene was amplified by nested PCR directly from clinical samples from trachoma or urogenital infection and the serovar of the infecting C trachomatis was determined by restriction fragment length polymorphism (RFLP). Amplified DNA from trachoma serovars B, Ba and C and from urogenital serovars Ba, C, D and E was sequenced by the dideoxy chain termination method. RESULTS--While almost identical in variable segment (VS)I, three urogenital Ba samples differed from all trachoma B and Ba samples at eight nucleotides including two sites which changed amino acids in the constant region upstream of VSI. An identical sequence in this region was observed for the reference urogenital D serovar. Variation in this same region upstream of VSI also distinguished 40% of serovar D samples from prototype D including three that were sequenced. Two urogenital C differed from trachoma C samples at four sites that changed the MOMP amino acid sequence including two changes in the constant region between VSII and III and single changes in VSII and III. On the basis of these sequence determinations, RFLP was predicted which allowed extension of these observations to 20 other urogenital Ba, 12 trachoma B or Ba, seven variant D, 12 D, four urogenital C and three trachoma C samples without further sequencing. CONCLUSION--Urogenital Ba and C samples have VSI or II and III sequences identical or very similar to trachoma strains of the same serovar, but resemble more closely other serovars in the constant regions. Urogenital serovar D samples can also be divided into two genotypes on the basis of sequence differences in the constant region preceding VSI.